HUBUNGAN PENGETAHUAN DENGAN KESIAPSIAGAAN IBU HAMIL DALAM MENGHADAPI BENCANA GEMPA BUMI DI WILAYAH KERJA PUSKESMAS PASAR IKAN KOTA BENGKULU - Dewi Aprilia Ningsih; Ruri Maiseptya Sari; Metha Fahrian; Ayu Permatasari (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2022)
The main cause that resulted in the emergence of many victims due to earthquake disasters is due to lack of knowledge of community preparedness about disasters and lack of community readiness in anticipating the disaster. This research aims to study the relationship of knowledge about disaster sustainability with the preparedness of pregnant women in the face of earthquake disasters in the working area of the Bengkulu City Fish Market Health Center. This research uses an Analytical Survey approach with cross sectional design. The population of this study is all pregnant women TM III in the working area of the Fish Market Health Center as many as 48 people, samples taken in total sampling. Data collection is using skunder and primary data. Data analysis was conducted with the Chi-Square (?2) and Contingency Coefficient (C) tests. The results of the study were obtained: (1) Of the 48 samples there were 19 people (39.6%) less prepared in the face of earthquake disasters and 29 people (60.4%) were ready to deal with earthquakes.